(untitled) (IAHS Medical Journal, 2025)
Background: Expansion of the bone marrow and secondary skeletal and craniofacial deformity are mainly seen in poorly treated thalassemic patients. Craniofacial anthropometry is a useful method that assists clinicians to identify deformities. The purpose of this study was to assess the craniofacial characteristics in transfusion dependent thalassemic patient in Bangladesh. Materials and methods: This cross-sectional analytical study was conducted during the period from October 2021 to September 2022 in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 100 respondents (50 transfusion dependent thalassemia patients and 50 non-thalassemic healthy individuals) of 5-30 years. Digital slide caliper and tape were used to measure 10 anthropometric parameters (6 horizontal, 3 vertical, and 1 head circumference) in cranial, facial, nasal and orbital zones. For statistical analysis Mann-Whitney U test was done and pvalue was considered significant if it was <0.05 at 95% level of confidence. Results: This study showed a significant difference (p = 0.012) between mean values of intercanthal width in transfusion dependent thalassemia patients and non-thalassemic healthy individuals. The difference between the head circumference, facial and nasal zone parameters of transfusion dependent thalassemia patients and non-thalassemic healthy individuals was not found to be statistically significant (p > 0.05). Conclusion: The baseline data from the study will help us better understand the craniofacial structure of thalassemic patients who rely on transfusions and will also allow us to get satisfactory results in diagnosing and treating their craniofacial illness. IAHS Medical Journal Vol 7(2), December 2024; 9-13